Syndromic infertility - Guerri, Giulia; Maniscalchi, Tiziana; Barati, Shila; Dhuli, Kristjana; Busetto, Gian Maria; Del Giudice, Francesco; De Berardinis, Ettore; De Antoni, Luca; Miertus, Jan; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2019)
Infertility due to genetic mutations that cause other defects, besides infertility, is defined as syndromic. Here we describe three of these disorders for which we perform genetic tests. 1) Hypopituitarism is an endocrine syndrome characterized by reduced or absent secretion of one or more anterior pituitary hormones with consequent dysfunction of the corresponding peripheral glands. Deficiencies in all the hormones is defined as pan-hypopituitarism, lack of two or more hormones is called partial hypopituitarism, whereas absence of a single hormone is defined as selective hypopituitarism. Pan-hypopituitarism is the rarest condition, whereas the other two are more frequent. Several forms exist: congenital, acquired, organic and functional. 2) The correct functioning of the hypothalamic-pituitary-gonadal axis is fundamental for sexual differentiation and development during fetal life and puberty and for normal gonad function. Alteration of the hypothalamic-pituitary system can determine a condition called hypogonadotropic hypogonadism, characterized by normal/low serum levels of the hormones FSH and LH. 3) Primary ciliary dyskinesia is frequently associated with infertility in males because it impairs sperm motility (asthenozoospermia). Primary ciliary dyskinesia is a group of genetically and phenotypically heterogeneous disorders that show morpho-structural alterations of the cilia. Adult women with primary ciliary dyskinesia can be subfertile and have an increased probability of extra-uterine pregnancies. This is due to delayed transport of the oocyte through the uterine tubes.